Effects of Space Allowance and Marketing Strategy on Growth Performance of Pigs Raised to Heavy Market Weights - A. B. Lerner; M. D. Tokach; J. M. DeRouchey; S. S. Dritz; R. D. Goodband; T. G. O'Quinn; J. M. Gonzales; E. A. Rice; M. W. Allerson; H. E. Price; J. C. Woodworth (Kansas Agricultural Experiment Station Research Reports, 2018)
A total of 976 pigs (PIC 327 × L42, initially 48.6 ± 3.4 lb body weight [BW]) were used in a 160-d growth study to determine the influence of space allowance and marketing strategy on growth performance of pigs raised to heavy market weights. Pens were blocked by location within the barn and allotted to 1 of 6 dietary treatments with 8 pens per treatment. The first four treatments reduced space allowance per pig via initial pen stocking density and had only one final marketing event. These four treatments were: 14 pigs/pen (12.7 ft2/pig), 17 pigs/pen (10.4 ft2/pig), 20 pigs/pen (8.8 ft2/pig), 23 pigs/pen (7.7 ft2/pig). The fifth treatment began with 25 pigs/pen (7.1 ft2/pig) and the heaviest 3 pigs/pen were removed on d 93, then on d 122 they were topped again to a common inventory of 20 pigs/pen, and on d 147 topped to a common pen inventory of 17 pigs/pen. The sixth treatment began with 23 pigs/pen (7.7 ft2/pig) and was topped to a common inventory of 20 pigs/pen on d 108 and finally topped again to a common inventory of 17 pigs/pen on d 147. Average daily gain (ADG), average daily feed intake (ADFI), and final BW decreased (linear,P<0.001) during the overall experimental period (d 0 to 160) as space allowance decreased. When comparing treatments with multiple marketing events to those with similar initial stocking density (23 pigs per pen), there was no evidence for differences (P>0.05) for overall ADG or ADFI; however, overall feed efficiency was improved (P<0.05) for pigs initially stocked at 7.1 ft2/pig and marketed four times compared to both treatments that initially allowed 7.7 ft2/pig, regardless of marketing structure. Additionally, overall F/G was improved for pigs that began at 7.7 ft2/pig and had 3 marketing events compared to the treatment that also began at 7.7 ft2/pig but had only a single marketing event. Once the marketing events began on d 93, ADG and F/G were improved (P<0.05) for the remaining pigs in the pen for the rest of the trial (d 93 to 160) for both multiple marketing treatments, compared to the 7.7 ft2/pig allowance where all pigs were marketed together at the end of the trial. These findings are consistent with others that evaluate more traditional market weights where growth performance is reduced prior to pigs reaching their k-value, and align with recent models that predict the rate of change in growth performance as pigs are allowed more spacing during the finishing period. Similarly, it appears that pigs respond to removal of the heaviest pigs in the pen before market with the remaining pigs in the pen demonstrating compensatory gain after being provided with increased space. These results indicate that decreasing space allowance for heavy weight pigs reduced growth, intake, and final BW, although use of pig removals prior to final marketing may allow producers to maximize number of pigs marketed while balancing reduced growth performance generally accompanied with increased stocking density. Additionally, growth continued to increase until approximately 340 lb, indicating a potential opportunity for swine producers to capture lean growth at much heavier weights than previously predicted.
Keywords: heavy weight pigs; finishing pigs; space requirements